PENDIDIKAN MORAL: ANTARA HARAPAN DAN REALITAS - Abdul Rahman Barakatu (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2008)
The application of moral education has honest aim. The Educational Institution is expected able to educate every learner in order to have behavior based on valid moral code. They are honest, believable, altruistic, sensible, and able to make relationship without breaking norm and another good action. This hope can be enlarged. The out put of educational Institution is expected to have morality consistently in daily relationship among the society. Even though the reality shows that its aims and hope have been reached yet. The phenomenon seems that the behavioral diverge from moral value such as; cheating, dishonest, mass fighting, violence, exportation and so on. This moral diverge, of course has causality. The causality can be divided into four aspects, namely; cultural system, educational system, internal learner’s condition, and external influencing the learner’s psychological development.